The Role of Parents in Developing Intrapersonal Intelligence in Early Age Children 5-6 years in Nyogan Village, Muaro Jambi Regency, Jambi Province - Hindun, Hindun; Ismail Fahri; Sururuddin; Fenny Wulansari (Green Publisher, 2024)
This research aims to examine the role of parents in developing the intrapersonal intelligence of young children aged 5-6 years in Nyogan village, Muaro Jambi Regency, Jambi Province. Intrapersonal intelligence in this research is being able to understand himself well, including his strengths and weaknesses, easily accepting input and even criticism of himself, knowing what he wants and having ideals. This type of research is descriptive qualitative research, meaning that the work steps to describe an object, phenomenon or social setting are contained in narrative writing . The subjects of this research were parents and children aged 5-6 years. The object of research is the intrapersonal intelligence of early childhood 5-6 years old. Data collection techniques use observation, interviews and documentation. Data was analyzed through data reduction, data presentation and drawing conclusions. The results of this research are 1) parenting patterns in Nyogan village, Muaro Jambi Regency are in various ways ranging from authoritarian, democratic and permissive patterns 2). Intrapersonal Intelligence of Early Childhood in Nyogan Village, Muaro Jambi Regency It is an intelligence that is not permanent so that its development is not as easy as intellectual intelligence, because intrapersonal intelligence is an intelligence that changes, sometimes experiencing increases but not infrequently also experiencing decreases. 3) the role of parents in developing the intrapersonal intelligence of young children aged 5-6 years in Nyogan Village, Muaro Jambi district is by spending time with children, opening their eyes, hearts and ears to children, will make children trust their parents and make parents their only ones. the only place where children pour everything out.